Pelatihan Budidaya Maggot sebagai Alternatif Pakan Ikan di Desa Carawali - Bibin, Muhammad; Ardian, Ani; Mecca, Adiba Nuwaira (Universitas Muhammadiyah Sidenreng Rappang, 2021)
Commercial feed produced by the factory has a guaranteed quality and quantity. However, the problem is the price of commercial feed produced by factories that are getting more and more expensive and troubling to fish breeders, thus making fish breeders have to look for other alternatives to reduce the cost of feed. Cultivation of maggots or larvae of black soldier fly flies (Hermetia illicens) the right solution to overcome the problem in lieu of high-protein fish feed. Maggot cultivation training activities as an alternative to fish feed are carried out in Carawali Village. The implementation method is done by means of lectures, discussions and practices. The result of this community service activity is the amount of enthusiasm of participants to the training activities by evidenced that the active participants follow the activity from start to finish. In addition, many participants are active in discussion and question and answer sessions. So it can be concluded that the maggot cultivation training in Carawali Village went successfully and smoothly. The continuation of this PKM activity is to train the understanding and attitude of the trainees on the importance of organic waste management for maggot cultivation as an alternative to fish feed.